PUSAT KUCING JATINEGARA DENGAN PENDEKATAN URBAN AKUPUNKTUR - Putri Nurandini; Timmy Setiawan (Jurusan Arsitektur dan Perencanaan, 2023)
Physical degradation in the Jatinegara animal market area can be seen from the stalls that occupy the sidewalks. As a result, the sidewalks become dirty, smelly, and damp because animal waste is also jammed, causing pedestrians and motorists to suffer. Acupuncture urban planning is carried out to produce impact and quality for large scale urban areas by producing a chain reaction, where one project or design made at one point can have an impact or positive effect on other areas. Macro, meso, micro analyzes were carried out to understand more about the Jatinegara Animal Market. Data collection was taken from print media, interviews and observations. The design method uses an urban acupuncture approach. In the Jatinegara Animal Market area, several issues were found in the animal market area, namely the stalls of traders who eat the pedestrian street, so that it becomes dirty and slippery and causes traffic jams. The concept of